The Effect of Management Operations and Infrastructure Administration on Employee Performance (Study at the General Bureau of Politeknik Negeri Malang) - Sanawi Sanawi; Anung Prasetyo Nugroho; Willy Tri Hardianto (International Journal of Management and Business, 2026)
This study aims to analyze the effect of management operations and infrastructure administration on employee performance at the Infrastructure Unit of the General Bureau of Politeknik Negeri Malang. A quantitative approach was employed with data collected through questionnaires from 60 respondents selected via purposive sampling, comprising lecturers, educational staff, and general employees. Multiple linear regression was used for data analysis. The findings reveal that management operations significantly affect employee performance (t = 3.566; sig = 0.001), while infrastructure administration shows no significant partial effect (t = 1.669; sig = 0.122). However, both variables together exert a significant simultaneous effect (F = 18.895; sig = 0.000), with a coefficient of determination of 40.3%, indicating their combined contribution to performance outcomes. Based on these results, it is recommended that the Head of the General Bureau optimize management operations through structured planning, consistent guidance, and periodic evaluation; infrastructure administration be enhanced with digital integration for efficiency in documentation processes; and future research explore additional factors such as work motivation, job satisfaction, and leadership style using broader populations for generalization.